2007
DOI: 10.1093/nar/gkm659
|View full text |Cite
|
Sign up to set email alerts
|

MutDB: update on development of tools for the biochemical analysis of genetic variation

Abstract: Understanding how genetic variation affects the molecular function of gene products is an emergent area of bioinformatic research. Here, we present updates to MutDB (http://www.mutdb.org), a tool aiming to aid bioinformatic studies by integrating publicly available databases of human genetic variation with molecular features and clinical phenotype data. MutDB, first developed in 2002, integrates annotated SNPs in dbSNP and amino acid substitutions in Swiss-Prot with protein structural information, links to sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…Several excellent web tools are already available for mapping and viewing SNVs on 3D protein structures (Yue et al 2006; Singh et al 2008; Ryan et al 2009; Reva et al 2011). However, MuPIT provides several unique features not found in other tools.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several excellent web tools are already available for mapping and viewing SNVs on 3D protein structures (Yue et al 2006; Singh et al 2008; Ryan et al 2009; Reva et al 2011). However, MuPIT provides several unique features not found in other tools.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, users can examine thousands of SNVs from a database or cohort of interest (e.g., ESP6500, COSMIC, TCGA etc), and visualize the relationship between SNVs in 3D (SNVs located close to one another in three-dimensional space may in fact be distant from each other in one-dimensional sequence space). By contrast, SNPs3D (Yue et al 2006) and mutDB (Singh et al 2008) provide the user with a pre-determined list of SNVs in a structure of interest that have been reported in public databases, e.g., NCBI’s dbSNP (Sherry et al 2001) or UniProtKB’s Swiss Variant Pages (UniProt 2012). Similarly, LS-SNP/PDB (Ryan et al 2009) only supports SNVs reported in dbSNP whilst LS-SNP/PDB, Mutation Assessor, and mutDB do not permit viewing of multiple SNVs on a protein structure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The information on location, tissue type, and frequency of somatic mutations in tumor samples together with the cancer type can be obtained from COSMIC[16] and TCGA databases [17], while other resources, for instance, MutDB [18] and SwissVar [19], integrate the data on germline and somatic mutations for specific genes and diseases.…”
Section: Methodsmentioning
confidence: 99%
“…Using AJAX, this database has successfully enhanced the speed of data exchange with the server. 20 Whereas, AVIS-AJAX viewer of interactive signaling networks [http://actin.pharm.mssm.edu/AVIS2], a google gadget compatible web-based viewer of interactive cell signaling networks have employed AJAX with the usage of the libraries GraphViz, ImageMagic (PerlMagic) and overLib to increase its capability of visualizing the text-based signaling networks in no time. 21 Bobby-Joe Breitkreutz and his group have developed the Biological General Repository for Interaction Datasets (BioGRID) database (http://www.thebiogrid.org) to house and distribute collections of protein and genetic interactions from major model organism species.…”
Section: Examples Of Bioinformatics Systems With Ajax Technologymentioning
confidence: 99%